Bacteria responsible for antimonite oxidation in antimony-contaminated soil revealed by DNA-SIP coupled to metagenomics. Issue 5 (31st March 2021) - Zhang, Miaomiao; Kolton, Max; Li, Zhe; Lin, Hanzhi; Li, Fangbai; Lu, Guimei; Gao, Pin; Sun, Xiaoxu; Xu, Rui; Xu, Fuqing; Sun, Weimin
ABSTRACT: Antimony (Sb), the analog of arsenic (As), is a toxic metalloid that poses risks to the environment and human health. Antimonite (Sb(III)) oxidation can decrease Sb toxicity, which contributes to the bioremediation of Sb contamination. Bacteria can oxidize Sb(III), but the current knowledge regarding Sb(III)-oxidizing bacteria (SbOB) is limited to pure culture studies, thus underestimating the diversity of SbOB. In this study, Sb(III)-oxidizing microcosms were set up using Sb-contaminated rice paddies as inocula. Sb(III) oxidation driven by microorganisms was observed in the microcosms. The increasing copies and transcription of the arsenate-oxidizing gene, aioA, in the microcosms during biotic Sb(III) oxidation indicated that microorganisms mediated Sb(III) oxidation via the aioA genes. Furthermore, a novel combination of DNA-SIP and shotgun metagenomic was applied to identify the SbOB and predict their metabolic potential. Several putative SbOB were identified, including Paracoccus, Rhizobium, Achromobacter and Hydrogenophaga . Furthermore, the metagenomic analysis indicated that all of these putative SbOB contained aioA genes, confirming their roles in Sb(III) oxidation. These results suggested the concept of proof of combining DNA-SIP and shotgun metagenomics directly. In addition, the identification of the novel putative SbOB expands the current knowledge regarding the diversity of SbOB. Abstract : The aioA gene-containing Paracoccus, Rhizobium, Archromobacter and Hydrogenophaga were identified to play a major role in Sb(III) oxidation.